Sola Pulcherrima Super Solem - “More Beautiful than the Sun and Month” (Marian Prayer from Gertrude’s and Nawojka’s Prayer-Books) - Karolina Targosz (Folia Historica Cracoviensia, 2004)
A new critical edition of a collection of nearly one hundred Latin prayers connected with Gertrude of Poland (ca 1025-1108), Polish princess, wife of Izaslav of Kiev, has revived an interest in this exceptional example of literature and religiousness o f the eleventh century. The multiplicity of issues connected with the prayer book requires further consideration. An example might be the iconographic concord of prayers both with the accompanying miniatures and the works of art, which Gertrude encountered in the west as well as in the east -from Rhineland, where she was educated to Ruthenia, where she stayed longest. The paper examines the issue in relation to the Marian subject matter. A problem that has not as yet been touched upon is the history o f the prayers in the centuries that followed, as a singular example from the 15th century regarding one such prayer reveals. The prayers are mostly theocentric and Christocentric in character, but in many of them the intercessive role of St. Mary is evoked. In Ruthenia Gertrude was exposed to representations of the Deesis type, characteristic of eastern Christianity. From the prince’s box in St. Sophia’s Cathedral in Kiev she saw them in a form of three tondi, situated on the arch encasing the central apse, while in the apse itself was a monumental depiction of St. Mary-Oranta, eternal and omnipotent advocate in heaven, referred to in prayers as “oratrix celorum”. Of the four prayers directed exclusively to Mary two are laudatory and supplicatory and the other two just laudatory. The latter are characterized by a sophisticated literary form, division into phrases, employment of internal and external rhymes and a number of rhetorical figures (alliteration, oxymorons). A solar epithet appears here among others (“sola pulcherrima super solem”). A lot of Marian epithets, such as the Mother of God, Our Lady and the Queen of the whole world (“Dei genitrix”, “domina et regina totius orbis”) find their equivalent in one of the five miniatures. In prayer no. 86 the praise refers not only to the significance of St. Mary as the Mother of God, but to her purely feminine and maternal functions and her role of a participant and witness to the life and passion of Christ. They find their equivalents in Marian and Christological artistic series of the time. One of them is a series of scenes on the wooden door of the church Sankta Maria im Kapitol in Cologne, made ca 1050. The church was rebuilt by abbotess Ida, one of Gertrude’s aunts, who also funded the door. In this church Gertrude’s mother, Richeza, was buried. Gertrude could see the door during her stay in Rhineland in the years 1075-1076. A number o f depictions are included in miniatures in the manuscripts from the Ottonian epoch, e.g. a Scripture-Book of abbotess Hitda of Meschede from ca 1020, with an Annunciation scene. Gertrude knew a different presentation o f this scene from monumental mosaics in Kiev. The maternity o f St. Mary was presented in many different types of the Nativity. An exceptionally extended depiction in the eastern spirit, including a reference to apocryphal texts, is shown in one o f the Codex’ miniatures. Prayer no. 86 in its Polish, slightly transformed version appeared after several centuries in the so-called Nawojka’s Prayer Book, which most probably belonged to Natalia Bninska, nee Koniecpolska (ca 1463-1531) in a manuscript from the end of the 15th century. The manuscript was lost and today is known from a copy made in the first half of the 19th century, including a copy of the old silver cover - a box from the 17th century. According to the inscription on the box it was supposed to be St. Jadwiga, Duchess of Silesia’s (ca 1178-1243) collection of prayers; a tradition which was immediately questioned. It seems, however, to possess a grain of truth. Gertrude’s Codex, having changed hands many a time, was presented to the chapter o f the Cividale del Friuli Cathedral in 1229, where it has been kept since. It was presented by St. Elizabeth, Princess o f Thuringia at the instigation of her uncle Berthold, patriarch o f Aquilea. Elizabeth was Jadwiga of Silesia’s niece and Berthold was her brother. If the prayer had not been copied at the time when Gertrude’s Codex was in Cracow (and it was there as many as three times), then it could have been Jadwiga’s relatives who had it copied. At an unspecified time it was translated from Latin into Polish for Jadwiga or for the next generations of women in Poland and the translation was transformed until the 15th century version was reached.